The Right of Free Movement and the Access To Social Protection in the EU: The Economical Dimension. Notes on the Case Elisabeta Dano v Jobcenter Leipzig, C-333/13 - Guimarães, Daniela (UNIO – EU Law Journal, 2015)
This article seeks to analyse the impact of the Court of Justice of the European Union’s (CJEU) decision in the Dano judgement concerning the free movement of EU citizens and their cross-border access to social benefits. The debate about social tourism or welfare migration has been acrimonious in the last years. The Member States face new challenges concerning the possibility of excluding economically inactive European Union (EU) citizens from other Member States from special non-contributory social benefits. However, if on one hand we have the need to protect the financial sustainability of the Member States, as non-active EU citizens from other Member States can represent a burden on their social assistance systems, on the other hand, we also need to respect one of the EU’s most basilar principles: the prohibition of discrimination on grounds of nationality. The CJEU has decided that the economically nonactive citizens of other Member States can only claim equal treatment in regard to access to social benefits, when they have a right of residence under Directive 2004/38 in the host Member State.